Efficacy of Mycoparasite Fecal Fungi Lecanicillium lecanii against Rust Disease (Phakopsora pachyrhizi) at Soybean (Glycine max L. Merril) - Bintan R; Amin S. Leksono; Yusmani Prayogo (Natural B, Journal of Health and Environmental Sciences, 2012)
The obstacle of efforts to increase the production of soybean is rust disease caused by obligate the parasite fungus Phakopsora pachyrhizi. One type of biological agent used to control rust disease is a mycoparasite fungus Lecanicillium lecanii. The aim of this study was to determine the effective density of conidia L. lecanii fungus for rust disease control and its impact on soybean yields. The study using complete randomized block design, three replication. The  treatment was the density of conidia L. lecanii i.e 104/mL, 105/mL, 106/mL, 107/mL, 108/mL and control. Isolates of the fungus L. lecanii was propagated on potato dextrose medium agar (PDA) in petri dishes. At the age of 21 days after inoculation conidia was taken one gram, then it was diluted with 10 ml sterile water and counted with a haemocytometer to obtain conidia density appropriate with the treatment. Furthermore, any suspension of conidia L. lecanii was applied to soybean at age 49-70 days after planting that was attacked by rust disease. Data were analyzed by ANOVA with SPSS 16.0 for windows. The analysis showed that treatment with a density of conidia 108/ml have better efficacy, as shown by the low intensity of the attacks by 15.9% compared to controls reached 27.15%. These results are also followed by a high number of fill-pods on the treatment 108/mL as much as 54.4 pods, dry seed weight of 9.85 grams, dry weight of 100 seeds 8.73 grams. Therefore that  L. lecanii fungus with density of conidia 108/mL can suppress the development of rust disease, can be used as a biological agent for substitute of chemical fungicides.